‘I can now hear the pauses’: the narratives of L2 listening and vocabulary development through extensive viewing - Lanoke Intan Paradita; Haira Rizka; Banatul Murtafi’ah; Lutfi Ashar Mauludin; Gatot Prasetyo (Cogent Arts & Humanities)
Acquiring language rather than merely learning it, as Krashen suggests, contributes significantly to successful second language use, emphasizing the need for comprehensible and compelling input. This study explores how an English learner achieved proficiency, particularly in listening skills and vocabulary, through self-selected viewing. Utilizing a case study approach, this research examines the learner’s use of TV series as a primary source of English input. The extensive viewing of TV series allowed the learner to build familiarity with linguistic elements, thereby enhancing listening fluency. Despite initial challenges, the engaging nature of the series motivated the learner to watch all episodes (approximately 2,500 TV series episodes and 16 movies), contributing to significant improvement. The study highlights the role of captions in this process, demonstrating how they facilitated vocabulary acquisition and supported listening skill development by providing simultaneous reading and listening opportunities. The learner’s strategy of using captions to practice speaking and verify pronunciations was crucial for developing listening fluency. The study notes that while narrow viewing benefited vocabulary and listening skills, further research is needed to explore its impact on other language skills and the influence of personality and affective factors on language acquisition.